Penggunaan Figma dalam Meningkatkan Kreativitas Siswa Sekolah Menengah Kejuruan Rekayasa - Syakh Alam, Helmy; Suaryani, Nanik; widiarti, ayunovi; Astawa, Dady; Dahana, Bayu; Ngurah Agung, Gung Bagus (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
User interface (UI) and user experience (UX) design play an important role in digital application development. However, Vocational High School (SMK) students often experience limitations in learning these skills due to minimal access to relevant training. This study aims to explore the use of the Figma application in improving the creativity of SMK Engineering students, especially in making presentations and UI/UX design. The implementation method of the activity includes an introduction to the basic concepts of UI/UX, training in the use of Figma features, and the application of the Design Thinking approach in the learning process. The results of the training showed a significant increase in the understanding of UI/UX concepts by 75%, the ability to use basic Figma features by 80%, and an increase in student creativity by 70%. In addition, Figma's real-time collaboration feature has been shown to support more dynamic interactions and accelerate the design process. Based on these findings, it is concluded that the integration of Figma in learning can effectively improve students' digital skills and creativity. It is recommended that Figma be included in the SMK curriculum to support students' readiness to face the needs of the digital creative industry.